Strategic Analysis: Case Study On HSBC Banking Corporation - Khaltar, Battur (2009)
This studi is to examine and evaluate the actions in terms of strategic management content in the real world particularly, in the banking corporation. It also evaluated the real world strategy of the organization in banking sector.